A study of the neurodegenerative mechanisms of Alzheimer’s and Huntington’s diseases - Parry, Nicholas (2016)
Axonal degeneration is a hallmark feature of numerous neurological conditions; one suggested cause of this degeneration is an accumulation of the NAD precursor molecule nicotinamide mononucleotide (NMN), which has been found to signal for cellular apoptosis following axonal injury. Upon treatment with the NAMPT inhibitor FK866 the accumulation of NMN is prevented and axonal survival rate is increased. A similar improvement in axonal survival is shown when nicotinamide mononucleotide adenylyltransferase 2 (NMNAT2), the enzyme responsible for conversion of NMN to NAD is present in excess. Previous studies have indicated that FK866 reduces the occurrence of axonal dystrophies and axonal swellings in Alzheimer’s disease (AD) and Huntington’s disease (HD) models respectively, my study seeks to expand on these findings by assessing the effect of FK866 on amyloid plaques in AD mice and nuclear aggregates of mutant huntingtin in HD mice, as well as exploring a potential interaction between Huntingtin (Htt) and NMNAT2. No evidence was found to suggest a direct bind between NMNAT2 and Htt, although an indirect interaction cannot be ruled out. My results indicate that while neither medication was found to be effective at reducing amyloid plaque count in the AD model both medication groups showed a reduction in plaque size, potentially accounting for previous findings of a reduced number of axonal dystrophies. It was found that FK866/NA promoted the formation of nuclear aggregates of mHtt in HD model mice while showing no negative cognitive effects, this warrants future study as the role of nuclear aggregates is currently still debated within the literature.